Antibody Survey of Bovine Viral Diarrhea in Bali Cattle - Sudipa, Putu Henrywaesa; Sudimartini, Luh Made; Wirata, I Wayan (Journal of Veterinary and Animal Sciences; Vol 3 No 1 (2020)DO - 10.24843/JVAS.2020.v03.i01.p02, 2020)
Bovine Viral Diarrhea (BVD) or malignant diarrhea in cattle is one of the animal diseases that causes economic losses in the cattle industry worldwide. The biggest economic loss due to infection by Bovine Viral Diarrhea is related to reproductive and calf disorders that continue to transmit the virus to other cattle. This study aims to determine the presence of Bovine Viral Diarrhea antibodies in Bali cattle. The sample uses Bali cattle’s blood from 30 cows that are accommodated in 2 tubes that contain anti-coagulant and which do not contain anti-coagulant. After being processed to get serum, plasma and buffy coat cells, then the samples were examined using the ELISA method and presented descriptively. The results showed that there were positive suspects in Sobangan village, Badung with 8 out of 15 samples (53%) and positive suspects in the village of Payangan, Gianyar with 3 out of 15 samples (20%). Positive results are influenced by biosecurity of each type of sample farm, in Sobangan village is a large farm so biosecurity is difficult to implement and the spread of disease is faster than in Payangan village that have small farm type.